Preparation and electrochemical performance of multilayered Ni(OH)2 nanoflakes with different orientations uniformly anchored on reduced graphene oxide sheets. (March 2021) - Lai, Liuqin; Lin, Yueming; Su, Siyu; Zhang, Liang; Cui, Yifan; Guo, Naili; Zhu, Xiaohong
Highlights: Orientation-controllable Ni(OH)2 nanoflakes uniformly anchored on rGO are prepared. The ammonia content tailors the orientation of Ni(OH)2 nanoflakes. High specific capacitance of 1770 F/g is obtained in Ni(OH)2/rGO composite. The Ni(OH)2/rGO electrode shows high rate capability and cycling stability. Abstract: Different orientations of multilayered Ni(OH)2 nanoflakes uniformly anchored on reduced graphene oxide (rGO) sheets are prepared by a facile chemical deposition method. It is found that vertically oriented Ni(OH)2 /rGO has a greater specific capacitance than the horizontally oriented counterpart. The electrochemical performance of as-fabricated vertically oriented Ni(OH)2 /rGO composite as cathode material for supercapacitors shows an unexceptionable specific capacitance along with high rate capability and cycling stability. As a result, the specific capacitance reaches 1770 F/g at a current density of 1 A/g in 6 M KOH solution. Furthermore, the Ni(OH)2 /rGO electrode displays an ultrahigh rate capability (maintaining 864 F/g at a high current density of 50 A/g) and a super cycling stability (142.2% capacity retention after 3000 charge-discharge cycles). Such an orientation-controlled Ni(OH)2 /rGO composite is thus a promising electrode material for great applications in energy storage systems.